ANALISIS BANTUAN HUKUM MELALUI ARBITRASE SYARIAH DALAM MENYELESAIKAN SENGKETA PERBANKAN SYARIAH - Muslih (PRANATA HUKUM, 2020)
Legal aid had the meaning of access to justice, which was the ability of people to seek and obtain restoration of their rights only through formal and informal justice court. The provision of legal aid providers in Law Number 16 of 2011 was a guarantee of the constitutional rights for the person or group of people which were categorized as poor people. Political law was something which underlies the basic policy of the promulgation of a regulation and the basic policy of the enactment of a certain regulation in the national legal system. The regulation and enforcement of sharia banking regulations in Indonesia from a political perspective of Islamic law was to be understood worthily, the existence of sharia banking regulations in Indonesia currently strengthened the theory of positivism of Islamic law and strengthened the paradigm of prophetic legal in the national legal system. According to the authors, the regulations contained in Law Number 16 of 2011 concerning legal aid, the most important thing was to provide legal assistance as a tool in law enforcement and justice. The legal assistance can be carried out in existence when the subject of legal aid, law enforcers and law institutions of sharia arbitration (Basyarnas) was functioning properly. Occasionally, the political view of Islamic law which had the main objective was the formation of justice products based on the Qur'an, Al-Hadith, Ijma and Qias in the concept and practice levels. Then the implementation of Law Number 16 of 2011 concerning legal assistance by Shari'ah arbitration in resolving Islamic banking disputes, with clear processes or mechanisms and agreements, arbitration agreement clauses before or after related to the agreement from the beginning was to provide convenience in resolving banking disputes or non banking disputes.